Plataforma de recomendación de habilidades tecnológicas según puesto de trabajo para profesionales de TI, en función de la demanda en las bolsas de trabajo digitales - Sanchez Bermudez, Diandra Esli (2020)
The global landscape is changing rapidly, the speed of technological advances, automation and digital transformation make business models and their objectives create multidisciplinary jobs with diverse knowledge, likewise companies compete to hire the best professionals, That is why it is essential to have unified and centralized information that provides a vision of what the labor market is looking for. This project proposes the development of a platform that helps people to visualize the technical skills that the labor market requires with greater demand for a job and to provide them with a general visibility based on the analysis of the most important job boards in the country , as well as the suggestion of organizations where to study them. This platform will be based on the use of emerging technologies such as natural language processing and scraping, to extract and analyze the technical skills demanded in the jobs of the main digital labor exchanges. Therefore, it can be concluded that the information generated will provide a professional orientation that they must still acquire to achieve their objectives, as well as the organizations where they can study them. This proposal could additionally provide growth such as the processing of information to evaluate hiring trends that can be used to inform and guide decisions, as well as the creation of educational content according to the real needs of people.